Karakteristik Morfologi dan Anatomi, serta Kandungan Klorofil Lima Kultivar Tanaman Penyerap Polusi Udara Sansevieria trifasciata. - Rita Megia; Ratnasari; Hadisunarso (Jurnal Sumberdaya Hayati, 2015)
Sansevieria trifasciata is an unique houseplant that can provide clean air to occupied room because it can absorb harmful substances from the air. This research aim to compare morphological, and anatomical characters and chlorophyll content of five cultivars of this plant. Morphological characters of all S. trifasciata cultivars observed varied in pattern, colour, and size of the leaf. Stomata can be found on both leaf surfaces; abaxial side have higher stomatal density than adaxial side. Distribution of single stomata was presented in all cultivars, while clustered stomata were also found in cv. Moonsine. Among all cultivars, stomatal density and stomatal index were found the highest in cv. Moonsine. The highest chlorophyll content, the longest leaf, widthest leaf and the thinnest leaf were found in cv. African Dawn. Potentially, S. trifasciata cv. African Dawn and S. trifasciata cv. Moonsine could absorb air pollution better than the other cultivars.